NicaForestal S.A. - Flores Cerda, Gerald Horacio; Bravo M., José Francisco (Managua (Nicaragua), 2015)
(En)
Ilus.; 1 ref., Contiene CD con registro CD0078/16 y misma clasificación
Tesis ((Lic Agr Neg)
Keywords: DESARROLLO EMPRESARIAL; PASANTIAS; CHONTALES